The ESCC Newsletter : October 2024 - English Speaking Catholic Council (2024)
Number of pages: 7

The ESCC Newsletter : August 2024 - English Speaking Catholic Council (2024)
Number of pages: 8

The ESCC Newsletter : April 2024 - English Speaking Catholic Council (2024)
Number of pages: 7

English Speaking Catholic Council : 2023-2024 Annual Report - English Speaking Catholic Council (2024)

Annual Report 2022-2023 - English Speaking Catholic Council (2023)

2021-2022 Annual Report - The English Speaking Catholic Council (2022)

Statement on Bill 96 : An Act Respecting French, the Official and Common Language of Quebec - The English Speaking Catholic Council (ESCC) (2021)

[Letter of Support re: Fulford Residence] - Celani, Paula; The English Speaking Catholic Council (ESCC) (2021)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

One Voice Coalition - Farrow, Anna; Wong, Judy (2020)

2019-2020 Annual Report - The English Speaking Catholic Council (ESCC) (2020)

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

[Letter to M. Sebastien Proulx, Minister of Education] - Lemay, Diane (2017)

[Lettre à M. Sébastien Proulx Ministre de l’Éducation] - Lemay, Diane (2017)

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

The English Speaking Catholic Council: The Thirty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (2016)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

[Carter Statement] - The English Speaking Catholic Council (ESCC) (2015)

Letter of Support for QCGN - Zucchi, John (2014)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

Loyola High School: How to Defend Religious Freedom - Allen, Paul (2014)

Consultation générale et auditions publiques sur le projet de loi n° 60 - The English Speaking Catholic Council (ESCC) (2013)
Le Conseil catholique d'expression anglaise (CCEA) s’oppose à la charte proposée par le projet de loi 60, et ce, pour les raisons suivantes : • Il menace d’éroder, d’un point de vue historique et juridique, les libertés fondamentales de conscience, de religion, d’opinion et d’expression. Il s’agit des libertés « primordiales » dans notre société et il faut s’opposer à tout ce qui tend à diluer ou à réduire ces libertés. • Il propose une société sécularisée dans laquelle l’expression et la pratique religieuses sont marginalisées. Il cherche à recadrer le débat public de manière à ce que l’exercice des droits et libertés protégés par les chartes soit perçu comme imposé à la société et nécessitant la permission de l’État. • Il formule une notion embrouillée de la séparation de l’Église et de l’État en proposant que l’État a le pouvoir de définir la nature des croyances, de la pratique et de l’expression religieuses. • Dans tous les points susmentionnés, il situe le rôle de l’État au-dessus des paramètres de gouvernance appropriés d’un gouvernement élu démocratiquement et responsable. Le CCEA demande au gouvernement du Québec de retirer le projet de loi 60.

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

Resolution re : Bill 14 - Donovan, Paul (2013)

Resolution re : Bill 14 - Donovan, Paul (2013)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

Communications Assembly June 9, 2012 : Brief from the English Speaking Catholic Council - McDaid, Mary (English Speaking Catholic Council, 2012)
The English Speaking Catholic Council appreciates the opportunity to participate in this General Assembly convened by Bishop Thomas Dowd on the future of communications within the English Sector of the Archdiocese of Montreal.

[Letter for St Gabriel School] - McDaid, Mary (2011)

[La religion en éducation pour les enfants] - McDaid, Mary (2011)

[Religion in Early Childhood Education Facilities and Daycare] - McDaid, Mary (2011)

Directives on Daycares - The English Speaking Catholic Council (ESCC) (2011)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Statement Regarding the Situation of the Catholic Times - The English Speaking Catholic Council (ESCC) (2010)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Soumis au Comité spécial Mourir avec Dignité par Le conseil catholique d’expression anglaise - The English Speaking Catholic Council (ESCC) (2010)
En 1980, nous, un group d’individus représentant divers secteurs de la communauté Catholique anglophone et ses organisations, nous sommes réunis dans le but de consolider nos ressources humaines et matérielles, en vue du développement de notre communauté. Cela a mené, en 1981, à la création du Conseil catholique d’expression anglaise (CCEA), ayant le mandat d’agir comme point central dans la coordination de la communauté Catholique anglophone de la région urbaine de Montréal. Au cours des ans, l’CCEA a assumé un rôle plus proéminant, élargissant son activité à toute la province et au-delà. S’inspirant de la compréhension Catholique contemporaine du rôle de la communauté laïque dans le monde moderne, Le conseil catholique d’expression anglaise aide à promouvoir les valeurs de sa communauté, et défend ces valeurs dans le processus de résolution des problèmes ayant un impact sur cette communauté. Le conseil d’administration se compose d’hommes et de femmes du secteur public et privé, tous bénévoles, qui s’engagent à appuyer leur communauté dans les domaines de l’éducation, de la santé et des services sociaux, de l’animation sociale, de la culture et de la justice sociale.

Submitted to the Select Committee on Dying with Dignity - The English Speaking Catholic Council (ESCC) (2010)
In 1980, a group of individuals who represented various sectors of the English-speaking Catholic community and its organizations met with the idea of consolidating our human and material resources for the development of our community. This led to the formation in 1981 of the English Speaking Catholic Council (ESCC) with a mandate to act as a focal point in coordinating the English-speaking Catholic community of Greater Montreal. Over the years, the ESCC has assumed a higher profile which now extends throughout the Province and beyond. Inspired by the contemporary Catholic understanding of the role of the laity in the modern world, the English Speaking Catholic Council assists in the promotion of its community’s values and advocates those values in the resolution of issues affecting this community. The Board of Directors is made up of women and men from both the private and public sectors, all volunteers, who come together with a commitment to support their community in education, health and social services, community animation, culture and social justice.

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

Church in the Modern World : Sociologist's View - Allen, Paul (2010)

The Twenty-Eighth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2009)

Déclaration sur le projet de loi 21 : Loi sur la laïcité de l’État - The English Speaking Catholic Council (ESCC) (2009)
Le Conseil catholique d’expression anglaise a été fondé en 1981 avec la mission d'agir comme catalyseur, rassembleur et facilitateur de l'action collective pour la communauté catholique anglophone au Québec. En tant qu'organisme inspiré par l'enseignement social catholique, le Conseil se préoccupe du bien commun et s’inquiète donc des implications du projet de loi 21 (Loi sur la laïcité de l'État) pour le bien-être social et civique de la société québécoise. Pour l’essentiel, les objections du Conseil à l'égard de la législation actuelle sont semblables à celles que nous avons exprimées dans notre mémoire de 2013 sur le projet de loi 60 (Charte affirmant les valeurs de la laïcité d'État, de la neutralité religieuse et de l'égalité entre les femmes et les hommes, et fournissant un cadre pour les demandes d'accommodement).

Statement on Bill 21 : An Act Respecting the Laicity of the State - The English Speaking Catholic Council (ESCC) (2009)
The English Speaking Catholic Council (ESCC) was founded in 1981 with the mission to act as a catalyst, convener and facilitator of collective action for the English-speaking Catholic community of Quebec. As an organization inspired by Catholic social teaching, the Council is concerned for the common good and is apprehensive as to the implications of Bill 21 (An Act respecting the laicity of the State) for the social and civic welfare of Quebec society. In the main, the objections the Council have regarding the current legislation are similar to those we expressed in our 2013 brief on Bill 60 (Charter affirming the values of State secularism and religious neutrality and of equality between women and men, and providing a framework for accommodation requests)1 However, there are a number of critical differences between the 2013 legislation and that introduced in 2019.

Freedom of Religious Instruction : A Fundamental Right of Parents and Children - Murphy, Martin P.; The English Speaking Catholic Council (ESCC) (The English Speaking Catholic Council (ESCC), 2008)
From the time it was proposed in the late 19809s to shift the Quebec school system from a denominational model to a linguistic one, the English Speaking Catholic Council (ESCC) has consistently fought for freedom of religion and parental choice in religious instruction for people of all faiths. Time and again, the ESCC has defended these principles in its submissions to the National Assembly, the Commission for the Estates-General on Education, the Special Joint Committee of the House of Commons and the Senate, and most recently, the BouchardTaylor Commission on Reasonable Accommodation of Minorities.

The Twenty-Seventh Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2008)

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Accommodements raisonnables et liberté de religon au Québec - Conseil catholique d’expression anglaise (2007)

Accommodements raisonnables et liberté de religion au Québec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Reasonable Accommodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)
We agree with the Commission that “the management of diversity, especially religious diversity... appears above all to pose a problem.” The appearance of a problem seems to have been provoked in large measure by post 9/11 “alarmist media coverage.” Careful reflection will show that there is no problem in reality and that the alarm is not worthy of Quebecers. The ESCC therefore counsels strongly against the temptation to tamper with the current constellation of relevant rights and privileges in Quebec; it is a product of the unique evolution of Quebec society and functions well as “a fair, original model of collective life of which we are proud.”

Reasonable Accomodation and Freedom of Religion in Quebec - The English Speaking Catholic Council (ESCC) (2007)

Seniors are an Asset for Quebec - Lincoln, Clifford (2007)

Ethical Guidelines Handbook for the Catholic Laity in Apostolic Service - The English Speaking Catholic Council (ESCC) (2007)

Consultation publique sur les conditions de vie des aînes : Un enjeu de société, une responsabilité qui nous interpelle tous - Conseil catholique d'expression anglaise (2007)
Le Conseil catholique d’expression anglaise aimerait féliciter le gouvernement du Québec pour avoir reconnu l’importance des problèmes affectant les aînés et notre population vieillissante et pour avoir créé le poste de ministre responsable des Aînés. Nous accueillons avec plaisir l’initiative de Mme Marguerite Blais, ministre responsable des Aînés, de tenir des audiences publiques sur les conditions de vie des aînés au Québec. Cet enjeu constitue une grande source de préoccupations pour notre communauté et pour ses institutions au service des personnes âgées, dont l’expérience dans ce domaine est considérable.

Public Consultation on Seniors' Living Conditions : A Social Issue That is the Responsibility of Us All Quebecers - The English Speaking Catholic Council (ESCC) (2007)
The English Speaking Catholic Council would like to congratulate the Government of Quebec for recognizing the importance of issues related to seniors and an aging population and its establishment of the post of Minister Responsible for Seniors. We also welcome the initiative of Mme Marguerite Blais, the Minister Responsible for Seniors, to hold public hearings on seniors’ living conditions in Quebec, an issue on which our community and its institutions serving the elderly have considerable experience and great concern.

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

Mémoire présenté par le Conseil catholique d’expression anglaise sur les conditions de vie des aînés - The English Speaking Catholic Council (ESCC) (2007)

Report on the Proposed Ethics and Religious Culture Program - The English Speaking Catholic Council (ESCC) (2006)
We affirm the positive objectives of this program, namely: 1) To incorporate ethics and religion into public education; 2) To foster students’ capacity to know and express their moral and religious convictions within a pluralistic context; 3) To develop the capacity for meaningful dialogue about diverse moral and religious convictions; 4) To anchor this program in the distinctive cultural and religious heritage of Quebec. However, we recommend some major revisions to the program. Five interrelated areas stand out for us.

Rapport du Conseil catholique d'expression Anglaise relatif au projet de programme éthique et culture religieuse - Conseil catholique d'expression anglaise (2006)

The Twenty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2006)

The Twenty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2005)

Strategic Plan : 2005-2006 to 2008-2009 - The English Speaking Catholic Council (ESCC) (2005)

The English-speaking Catholic Population Profile in Quebec, 2001 : Comparative Analysis of the Demographic Characteristics and Geographic Distribution of the FOLS-English Catholic Population in Quebec - Ahmadzadeh, Nazanin (English Speaking Catholic Council, 2004)
The general objective of this study is to provide the English-Speaking Catholic Council in Québec with a comprehensive demographic portrait of the English speaking Catholic Community in Québec. This portrait will serve as support for the orientation of the ESCC. This study follows a previous study carried out in 1992 which focused only on the parishes in the Montreal metropolitan area.

The English-Speaking Catholic Population in Quebec, 2001 - Ahmadzadeh, Nazanin; Warnke, Jan (2004)

Gardez le lien avec la communauté - The English Speaking Catholic Council (ESCC) (2004)

Respect Minority and Community Rights in Any Health Care Reforms - The English Speaking Catholic Council (ESCC) (2004)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Mémoire du Conseil catholique d’expression anglaise sur la création de réseaux locaux de services de santé et de services sociaux à Montréal - Allmand, Warren (Conseil catholique d’expression anglaise, 2004)

The English-speaking Catholic Population Profile in Quebec, 2001 - English Speaking Catholic Council (2004)

The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)

The Twenty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2003)

The Twenty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2002)

Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

The Twentieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2001)